Concussion management knowledge among residents and students and how to improve it - Mohammad N Haider; John J Leddy; John G Baker; John M Kiel; Michael Tiso; Karl A Ziermann; Barry S Willer (Concussion)
Aim: Recognition and management of concussion is an area of growing importance. The objective was to measure concussion knowledge among residents and medical students (MS). Methods: Baseline knowledge was assessed by a standardized questionnaire. Control group (family medicine [FM], pediatric medicine [PM] and emergency medicine) residents were given reading material, and intervention group rotated in a clinic (sports medicine residents and MS). Subjects were retested after 36.82 (16.1) days. Pre- and post-intervention test scores were compared. Results: The average baseline knowledge scores were 79.2% for emergency medicine residents, 61.4% for FM, 68.5% for PM, 71.7% for sports medicine residents and 68.0% for MS. Knowledge increase for control group was 1.16% compared with 14.41% for the clinical rotation group (p < 0.0001). Conclusion: PM and FM residents can benefit from more focused education about concussion.